The Relationship Among Morningness-Eveningness, Sleep Duration, Social Jetlag, and Body Mass Index in Asian Patients With Prediabetes - Anothaisintawee, Thunyarat; Lertrattananon, Dumrongrat; Thamakaison, Sangsulee; Thakkinstian, Ammarin; Reutrakul, Sirimon (Frontiers in Endocrinology, 2018)
Background: Circadian system is known to influence energy metabolism. Recent evidence suggested that evening preference could be associated with higher body mass index (BMI). Moreover, evening preference is known to be associated with insufficient sleep duration and greater social jet lag, both described to be associated with obesity. This study aimed to explore whether morningness-eveningness was directly associated with BMI or its effect was transmitted through sleep duration or social jet lag in patients with prediabetes. Methods: A total 2,133 patients with prediabetes were enrolled. Morningness-eveningness was assessed using a Composite Scale of Morningness (CSM). Average weekly sleep duration and sleep timing were obtained, and social jet lag was calculated. BMI was calculated by weight (kg)/height2(m2). A mediation analysis was performed based on two pathways, CSM->sleep duration->BMI and CSM->social jetlag->BMI. A sequential equation model was used to estimate the direct and indirect effects of CSM on BMI. Results: Mean (SD) age and BMI were 63.6 (9.2) years and 25.8 (4.0) kg/m2. For CSMsleep durationBMI pathway, every one point decrease in CSM (more evening preference) was associated with a decrease in sleep duration by 0.054 h (95% CI 0.043-0.066), whereas sleep duration was negatively associated with BMI (coefficient = -0.156, 95%CI -0.288, -0.024). Mediation analysis indicated that a change in CSM (from 90th percentile to 10th percentile, more evening preference) was associated with a decrease in sleep duration and an increase in BMI by 0.102 kg/m2 (95% CI 0.015, 0.207). In addition, this change in CSM was directly associated with an increase in BMI by 0.511 kg/m2 (95%CI 0.030, 0.952). The CSMsocial jetlagBMI pathway analysis revealed that social jetlag was not significantly associated with BMI. A subgroup analysis in those aged ≤60 years (n=784) revealed that each hour increase in social jetlag was associated with an increase in BMI by 0.56 kg/m2 (p=0.026) while CSM and sleep duration were not. Conclusion: In patients with prediabetes, more evening preference was directly associated with higher BMI and indirectly through insufficient sleep duration, while social jet lag did not mediate the relationship between CSM and BMI. In those ≤60 years, only greater social jetlag